Evaluation of different types of fats for use in high-ratio layer cakes - Zhou, Jianmin (Kansas State University, 2010)
Shortening is a major ingredient used in high-ratio layer cakes. Plastic shortenings are most commonly used by the U.S. baking industry, but high levels of trans- or saturated fats cause health concerns. Compared to plastic shortenings, liquid shortenings could significantly reduce the dependence on high melting point fats and the emulsifiers used would enhance the shortening’s functionality. The objective of this research was to compare the influence of different types of fats on the texture and shelf-life of high-ratio layer cakes. Cakes were baked with soybean oil to evaluate the function of three emulsifiers (PGMS, GMS, and Lecithin) on layer cake quality, including volume, cake score, interior visual texture (C-Cell), and firmness (Voland-Stevens). An optimum emulsifier combination was chosen (PGMS 1.8%, GMS 1.0% and Lecithin 0.8%) for addition to the liquid oil. Four groups of layer cakes were baked using: plastic shortening, liquid shortening, liquid oil, or liquid oil plus emulsifier combination. Cake performance and firming over-time were evaluated. The liquid shortening provided the best fresh cake characteristics and cake firmness performance. Liquid oil combined with a combination of added emulsifiers performed very similar in terms of firmness, as did the liquid shortening. This indicated that emulsifiers played an important role on the improvement of cake firmness shelf-life.
Keywords: Cake; High Ratio; Fats; Emulsifiers; Agriculture, Food Science and Technology (0359)